Analysis of Program Issues on Tuberculosis Prevention Therapy - Rahma, Vidyana Aulia; Isfandiari, Muhammad Atoillah; Qurniyawati, Eny (Indonesian Journal of Global Health Research, 2024)
Tuberculosis remains a significant problem in Madiun. There are several issues in the TB program, particularly in the low coverage of Tuberculosis Prevention Therapy (TPT). Besides the low coverage of TPT, there are also significant gaps in the delivery of TPT at several health facilities. Based on the analysis of the issues related to the low coverage of the TPT program, not all health facilities have implemented TPT. Objective: Identifying priorities of problems until providing alternative solutions to problem solving. Method: This study is a qualitative, descriptive observational study. The population consists of all program managers at the Madiun City Health Agency, with seven individuals selected as samples. Problem identification was conducted through in-depth interviews. Prioritization of problems was achieved using the Urgency, Seriousness, and Growth (USG) methods. The prioritization of problems was analyzed using a fishbone diagram to determine the root cause of the issues. Results: Identified the priority problem as the low coverage of TPT due to various factors grouped into Man, Process, Material, and Market. Conslusions: Based on the analysis of priority issues using the USG method, the results show that the achievement of Tuberculosis Prevention Therapy is still low and has not reached the target. The analysis of the root causes of the problem using the fishbone method reveals that the limited number of personnel results in double job burdens, the preference of medication adherence monitor for family over cadres, and the difficulty inviting cadres for socialization.